Analisis Distribusi Biomassa Pada Vegetasi Mangrove Menggunakan Metode Spatial Interpolation Di Nusa Lembongan, Bali - Rahimah, Fariha; La Ode Alam Minsaris; Widiyanto, Kukuh (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
Mangroves are coastal ecosystems that have an important role in maintaining the balance of the coastal environment and are effective carbon absorbers which have an important role in climate regulation. The effects of global warming can be reduced through the absorption of organic carbon from photosynthesis and stored in woody biomass, such as standing mangrove trees. Biomass distribution analysis in mangrove vegetation is needed to understand the condition and distribution of mangrove vegetation in more depth and to reflect the productivity and health of the ecosystem. Nusa Lembongan Bali has the potential and utilization of mangrove ecosystems which have potential flora and fauna that need to be preserved. Method spatial interpolation is an effective approach in analyzing biomass distribution because it is able to overcome the limitations of sample data in large forest areas using deterministic techniques Inverse Distance Weighted (IDW). This research aims to analyze the distribution of mangrove vegetation biomass and assess the level of accuracy of the method spatial interpolation in producing a distribution map of mangrove biomass in Nusa Lembongan, Bali. There are 4 types of mangroves found in Nusa Lembongan that are affordable for research, including: Rhizophora apiculata, Xylocarpus granatum, Bruguiera gymnorrhiza And Sonneratia alba, with 90% having a sandy mud substrate. Nusa Lembongan has good biomass distribution as shown by the mangrove vegetation biomass distribution map which shows a dominant color of green to yellow with an average biomass value of 200 Mg/ha to 300 Mg/ha. The results of the correlation calculation have a significant correlation accuracy value with a value of rCount 0.997 > rTable 0.273 which is shown through the results of correlation calculations that support the results of biomass distribution in mangrove vegetation on Nusa Lembongan Island, Bali.